The mystification of the subatomic physics: causes and effects - Kozachenko, Nadija (Actual Problems of Mind, 2017)
The article examines the crisis in modern Elementary Particle Physics. There are substantive and methodological problems of science, resulting from rupture of physics and philosophy. For example, a popular String Theory shows as deformed science approaching to religion in their functions.